Tfl deletion induces extraordinary Cxcl13 secretion and cachexia in VavP-Bcl2 transgenic mice - Minagawa, Kentaro; Wakahashi, Kanako; Fukui, Chie; Kawano, Yuko; Kawano, Hiroki; Suzuki, Tomohide; Ishii, Shinichi; Sada, Akiko; Nishikawa, Shinichiro; Asada, Noboru; Katayama, Yoshio; Matsui, Toshimitsu (Frontiers in Immunology, 2023)
Statement of significance: Loss of TFL, found in several types of lymphoma, induces excessive CXCL13 secretion through RNA dysregulation contributing to body weight loss and early death in lymphoma model mice. Follicular lymphoma (FL) is associated with overexpressed BCL-2 and other genetic aberrations, including 6q-. We identified a novel gene on 6q25, “Transformed follicular lymphoma (TFL),” from a transformed FL. TFL regulates several cytokines via mRNA degradation, which has been suggested to underlie resolving inflammation. Fluorescence in situ hybridization revealed a deletion of TFL occurred in 13.6% of various B-cell lymphoma samples. We developed VavP-bcl2 transgenic, TFL deficit mice (Bcl2-Tg/Tfl-/-) to seek how TFL affects disease progression in this lymphoma model. While Bcl2-Tg mice developed lymphadenopathy and died around 50 weeks, Bcl2-Tg/Tfl-/- mice lost body weight around 30 weeks and died about 20 weeks earlier than Bcl2-Tg mice. Furthermore, we found a unique B220-IgM+ cell population in the bone marrow of Bcl2-Tg mice. cDNA array in this population revealed that Cxcl13 mRNA in Bcl2-Tg/Tfl-/- mice expressed significantly higher than Bcl2-Tg mice. In addition, bone marrow extracellular fluid and serum showed an extremely high Cxcl13 concentration in Bcl2-Tg/Tfl-/- mice. Among bone marrow cells, the B220-IgM+ fraction was the main producer of Cxcl13 in culture. A reporter assay demonstrated TFL regulates CXCL-13 via induction of 3’UTR mRNA degradation in B lineage cells. These data suggest Tfl regulates Cxcl13 in B220-IgM+ cells in the bone marrow, and a very high concentration of serum Cxcl13 arising from these cells may contribute to early death in lymphoma-bearing mice. Since several reports have suggested the association of CXCL13 expression with lymphoma, these findings provide new insights into cytokine regulation via TFL in lymphoma.